The Role of Regional Taxes and Regional Levies on Original Regional Income (PAD) in Majene Regency - Aldi (Yayasan Amerta Insan Unggul, 2022)
This study investigates the role of local taxes and regional levies in Majene Regency's local revenue. Utilizing qualitative methods, including literature study, observation, interview, and documentation, the research aims to shed light on the effectiveness and stability of local revenue (PAD) influenced by local taxes and regional levies. The findings reveal that the optimization of local taxes and regional levies remains a challenge, leading to fluctuating local revenue in Majene Regency, particularly during certain periods such as holidays. Despite the broad authority granted to regional governments, effective management and utilization of local revenue sources are crucial for supporting regional autonomy and development. Through interviews and data analysis, it becomes evident that while regional levies contribute significantly to local revenue, there are obstacles in their management, including insufficient personnel and public awareness. Furthermore, challenges such as economic conditions and payment trends affect local tax revenue. The study concludes with recommendations for improving revenue management, including exploring tourism potential, enhancing taxpayer data collection, conducting further research on different tax types, and fostering public compliance with tax obligations. By addressing these recommendations, Majene Regency can enhance its local revenue and support regional development effectively.